P002 Targeted non-CPAP combination therapy resolves obstructive sleep apnoea. (7th October 2021) - Aishah, A; Tong, B; Osman, A; Donegan, M; Pitcher, G; Kwan, B; Brown, L; Altree, T; Adam, R; Mukherjee, S; Eckert, D
Abstract: Introduction: Mandibular advancement splint (MAS) therapy is an effective alternative to CPAP for many people with obstructive sleep apnoea (OSA) but 50% have residual OSA. This study aimed to resolve OSA in these individuals by combining MAS with other targeted therapies based on OSA endotype characterisation. Methods: Eleven people with OSA (apnoea-hypopnoea index (AHI): 35±13 events/h), not fully resolved with MAS alone (AHI>10 events/h) were recruited. Initially, OSA endotypes were assessed via a detailed physiology night. Step one of combination therapy focused on anatomical interventions including MAS plus an oral expiratory positive airway pressure valve (EPAP) and a supine-avoidance device. Participants with residual OSA (AHI>10 events/h) following the anatomical combination therapy night, were then given one or more targeted non-anatomical therapies according to endotype characterisation. This included oxygen (4L/min) to reduce unstable respiratory control (high loop gain), 10mg zolpidem to increase arousal threshold, or 80/5mg atomoxetine-oxybutynin (ato-oxy) for poor pharyngeal muscle responsiveness. Results: OSA was successfully treated (AHI<10 events/h) in all participants with combination therapy. MAS combined with EPAP and supine-avoidance therapy resolved OSA in 65% of participants (MAS alone vs. combination therapy: 17±4 vs. 5±3, events/h, n=7). For the remaining participants, OSA resolved with the addition of oxygen (n=2), one with 80/5mg ato-oxy and another required both oxygen and 80/5mg ato-oxy. Discussion: Targeted combination therapy may be a viable treatment alternative for people with OSA who cannot tolerate CPAP or for those who have an incomplete therapeutic response with monotherapy.